Contribution of complementary operation in adapting to climate change impacts on a large-scale wind–solar–hydro system: A case study in the Yalong River Basin, China. (1st November 2022) - Cheng, Qian; Liu, Pan; Xia, Jun; Ming, Bo; Cheng, Lei; Chen, Jie; Xie, Kang; Liu, Zheyuan; Li, Xiao
Highlights: A model chain is constructed to quantify contributions of complementary operation. Future power curtailment risks of the WSHCS will increase. Energy production and reliability can be guaranteed in most future scenarios. The complementary operation can partly adapt to climate change impacts. Abstract: Operation flexibility of hydropower stations and regulation ability of reservoirs can complement intermittent wind and photovoltaic power to form a stable wind–solar–hydro complementary system (WSHCS). It is acknowledged that alteration of wind, solar, and water resources by climate change might degrade power generation of WSHCSs; however, comprehensive evaluation of the potential impact of climate change on the energy production, reliability, and power curtailment of WSHCSs remains lacking. Furthermore, quantification of the contribution of complementary operation of a WSHCS in adapting to climate change impacts represents another vital knowledge gap. To address these problems, this study constructed a top-down model chain by integrating global climate models, hydrological models, and energy system operation models. The large-scale WSHCS in the Yalong River Basin (China) was considered as a case study. Results indicated substantial complementarity among the variation of monthly streamflow, wind speed, and solar radiation under a changing climate. The total energy production and reliability of the WSHCS could be guaranteed under most future climate scenarios, while power curtailment risk would increase. Although climate change impacts dominate change in system operation performance, complementary operation can contribute a positive effect to a certain extent, especially for higher reliability and lower power curtailment. The findings indicate the effectiveness of the complementary operation in adapting to climate change impacts on the Yalong River WSHCS. The major novelty of this study is quantification of the contribution of complementary operation in adapting to climate change impacts on WSHCSs, which provides valuable insight regarding evaluation of complementary systems.